Understanding the reasons for Malaysian youth participation in volunteering activities - Hamzah, Siti Raba'ah; Suandi, Turiman; Arif Shah, Jasmin; Ismail, Ismi Arif; Hamzah, Azimi (Athens Institute for Education and Research, 2014)
This paper explores the reasons for Malaysian youth participating in volunteering activities and examines the variables that predict their participation. The subjects in the study were from the Department of Youth and Sports, Malaysia. A total of 251 respondents, between the ages of 15 to 25 (M age = 20.2, SD = 2.7), participated in this study. Using the Social Exchange theory as a framework for this study, three main factors contributing to youth participation in volunteering activities were the perceived benefits from volunteering (‘benefits’), the personal needs or fulfilment the respondents to volunteer (‘needs’), and their personal reasons for volunteering (‘reasons’). Our findings showed that the benefits included learning to shoulder responsibility, broadening interest, fostering relationships, building teamwork spirit, and encouraging socialisation within the community setting. The need to volunteer was associated with the desire to unleash leadership potential and improve communication skills. Finally, the reasons for volunteering included using leisure time meaningfully, getting new experience, improving confidence and self-esteem, attaining emotional stability, and getting a better understanding of the realities of life. The findings indicated positive relationships between participation and ‘benefits’, ‘needs’ and ‘reasons’ to volunteer. However, ‘reason’ was the strongest predictor of youth becoming volunteers. In the study; Pompidou Center (1977) which is a landmark in circulation area design’s, by giving examples of today’s museum buildings, Orsay Museum (1986) which was transformed into a museum from train station and Jean Nouvel’s Quai Branly Museum (2006) which is a recent example of this striking change has been analyzed thorough spatial experiences, observations, syntactic analysis technique and semantic examinations.